Evaluasi Keberlanjutan Penggunaan Aplikasi PLN Mobile Menggunakan Human-Computer Interaction dan Trust - Safina Bulan Koesasih; Siti Mukaromah; Eristya Maya Safitri (Bridge : Jurnal Publikasi Sistem Informasi dan Telekomunikasi, 2024)
In the digitalization era, mobile payment applications are highly sought after to facilitate financial activities. PLN has innovated by introducing PLN Mobile, which simplifies online electricity bill payments. Despite offering many conveniences, some users feel there are shortcomings and difficulties with this app, potentially affecting its continued usage. This thesis aims to evaluate the factors influencing users' decisions to continue using the application, utilizing a conceptual model that combines Human-Computer Interaction (HCI) and Trust based on research by Kaewkitipong et al. (2022). This model includes seven variables: skill, system quality, information quality, task-technology fit, HCI, trust, and continuance intention. Testing uses the SEM-PLS technique and is processed with SmartPLS 4 using a sample of 384 respondents. The results indicate that HCI and trust significantly influence continuance intention, while system quality, information quality, and task-technology fit significantly influence HCI. These findings provide insights for improving and enhancing the PLN Mobile service to encourage its sustainable use.